Computed tomography lesions and their association with global outcome in young people with mild traumatic brain injury - Riemann, Lennart; Mikolic, Ana; Maas, Andrew I.; Unterberg, Andreas; Younsi, Alexander; Sánchez-Porras, Renán (Journal of neurotrauma, 2023)
Mild traumatic brain injury (mTBI) can be accompanied by structural damage to the brain. Here, we investigated how the presence of intracranial traumatic computed tomography (CT) pathologies relates to the global functional outcome in young patients one year after mTBI. ...
Online veröffentlicht am 28. Dezember 2022
Gesehen am 28.11.2023